2023
DOI: 10.1177/13540688231155428
|View full text |Cite
|
Sign up to set email alerts
|

Length of candidate lists and political careers: Quasi-experimental evidence from Brazil

Abstract: This paper provides causal estimates of the effects of increases in the size of candidate lists on the political careers of newcomers to the political arena. We explore an exogenous discontinuity in district magnitude that allows parties to expand their candidate lists in the Brazilian open-list local elections and find that the additional candidacies are allocated to weaker candidates, mainly newcomers, who end up occupying a significant share of the additional seats. We also find that the electoral experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Most of the time, it requires candidates not just to run but to run and lose several times before getting elected. An extensive body of literature has shown that by running and losing, candidates can learn from their mistakes, become better known among donors and voters, and perform better in future elections (Anagol and Fujiwara, 2016; Campos Fernandez Hott and Menezes-Filho, 2023; Canon, 1993; Haime, Vallejo, and Schwindt-Bayer, 2022; Mack, 1998; Roberds and Roberts, 2002; Söderlund and von Schoultz, 2023; Squire, 1992). Therefore, if persistence as candidate increases the chances of getting elected, a key question to understanding women’s representation is thus: Are women more likely than men to give up politics after losing an election?…”
mentioning
confidence: 99%
“…Most of the time, it requires candidates not just to run but to run and lose several times before getting elected. An extensive body of literature has shown that by running and losing, candidates can learn from their mistakes, become better known among donors and voters, and perform better in future elections (Anagol and Fujiwara, 2016; Campos Fernandez Hott and Menezes-Filho, 2023; Canon, 1993; Haime, Vallejo, and Schwindt-Bayer, 2022; Mack, 1998; Roberds and Roberts, 2002; Söderlund and von Schoultz, 2023; Squire, 1992). Therefore, if persistence as candidate increases the chances of getting elected, a key question to understanding women’s representation is thus: Are women more likely than men to give up politics after losing an election?…”
mentioning
confidence: 99%